2020
DOI: 10.1371/journal.pone.0227060
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diet on the gastrointestinal microbiome of juvenile rehabilitating green turtles (Chelonia mydas)

Abstract: Threatened and endangered green turtles (Chelonia mydas) are unique because as juveniles they recruit from pelagic to near-shore waters and shift from an omnivorous to primarily herbivorous diet (i.e. seagrass and algae). Nevertheless, when injured and ill animals are admitted to rehabilitation, animal protein (e.g. seafood) is often offered to combat poor appetite and emaciation. We examined how the fecal microbiome of juvenile green turtles changed in response to a dietary shift during rehabilitation. We col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
2
28
1
2
Order By: Relevance
“…Investigations into the microbiota of reptiles, including sea turtles, are limited to studies describing microbial communities [16][17][18][19][20][21][22][23][24][25][26][27][28][29], factors that influence their composition [30][31][32][33][34][35][36][37][38][39][40][41][42][43], and how they affect host physiology [8,9,[44][45][46], but investigations into the influence of phylogenetic factors affecting microbiota composition in this taxon are rare. Irrespective of the potential host-phylogenetic signal in microbiota composition at a broad taxonomic level, it has been shown that at a more individual level, diet, captivity, geography, and feeding regime all influence the microbiota [9,17,32], and that fermenting bacteria are important for digestion in herbivorous species [47].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into the microbiota of reptiles, including sea turtles, are limited to studies describing microbial communities [16][17][18][19][20][21][22][23][24][25][26][27][28][29], factors that influence their composition [30][31][32][33][34][35][36][37][38][39][40][41][42][43], and how they affect host physiology [8,9,[44][45][46], but investigations into the influence of phylogenetic factors affecting microbiota composition in this taxon are rare. Irrespective of the potential host-phylogenetic signal in microbiota composition at a broad taxonomic level, it has been shown that at a more individual level, diet, captivity, geography, and feeding regime all influence the microbiota [9,17,32], and that fermenting bacteria are important for digestion in herbivorous species [47].…”
Section: Introductionmentioning
confidence: 99%
“…This pattern was also seen in turtle studies, with herbivorous species having gut microbiota dominated by Firmicutes (Gaillard, 2014;Modica, 2016;Fugate et al, 2019;Peng et al, 2020), while carnivorous and omnivorous species had gut microbiotas dominated by Bacteroidetes (Biagi et al, 2018;Bloodgood et al, 2020). In particular, Bloodgood et al (2020) showed that gut microbial diversity has the ability to change in relation to diet; when herbivorous green sea turtles (Chelonia mydas) were given an omnivorous diet (seafood + vegetables) in captivity, their gut microbiota shifted from being dominated by Firmicutes to Bacteriodetes. In our study, the proportion of Bacteroidetes was higher in captive S. bealei (12.37 ± 11.97% in WS, 24.94 ± 19.62% in CS), as well as Firmicutes (18.12 ± 13.65% in WS, 68.61 ± 22.97% in CS).…”
Section: Comparison Of Wild and Captive Individualsmentioning
confidence: 61%
“…A trend first found in humans, individuals with plant-based diets have gut microbiota dominated by taxa in the phylum Firmicutes that metabolize plant polysaccharides and degrade cellulose into volatile fatty acids, while animal-based diets are dominated by taxa in the phyla Proteobacteria that are bile tolerant (David et al, 2014). This pattern was also seen in turtle studies, with herbivorous species having gut microbiota dominated by Firmicutes (Gaillard, 2014;Modica, 2016;Fugate et al, 2019;Peng et al, 2020), while carnivorous and omnivorous species had gut microbiotas dominated by Bacteroidetes (Biagi et al, 2018;Bloodgood et al, 2020). In particular, Bloodgood et al (2020) showed that gut microbial diversity has the ability to change in relation to diet; when herbivorous green sea turtles (Chelonia mydas) were given an omnivorous diet (seafood + vegetables) in captivity, their gut microbiota shifted from being dominated by Firmicutes to Bacteriodetes.…”
Section: Comparison Of Wild and Captive Individualsmentioning
confidence: 74%
See 2 more Smart Citations